Ventilator-associated lung injury in the intensive care unit and operating room – what's new? - V. V. Kuzkov; K. S. Lapin; E. V. Fot; M. Yu. Kirov (Вестник анестезиологии и реаниматологии, 2020)
The prophylaxis of ventilator-associated lung injury (VALI) and postoperative pulmonary complications (PPC) is of utmost importance to reduce complications both in the perioperative period of major surgery and in the intensive care unit (ICU).Protective approach to mechanical ventilation comprises a wide range of measures reducing the damage of the lung tissue associated with the stress and strain phenomena. The implementation of the strategy of high positive end-expiratory pressure (PEEP) in combination with alveolar recruitment maneuver has numerous limitations and requires further personalized approaches.When lung injury is self-induced by a patient, it becomes an important contributor to VALI and should be timely diagnosed and prevented both before initiation of mechanical support and during the restoration of spontaneous breathing. This review highlights the key mechanisms of VALI and current understanding of protective ventilation. The concept of damaging energy as well as approaches to the personalized optimization of respiratory settings are discussed in detail. Particular attention is paid to the prognostication of the risk factors of VALI and PPC.